Dermatological Photography – Guidelines - Varnika Singh; Mukta; Shivakumar Harti; Shalini Rai; Vishnudutt Agrawal (Journal of Ayurveda)
Introduction: An image has the capability to describe things better than words. These lines are applicable, especially in the case of dermatological photography (DP). However, a good image can be obtained if one has good photographic guiding principles. In the present article, we report on the development of standard guidelines for DP. Development of dermatological photographic guidelines with consistency and uniformity. To ensure the best possible dermatological photographs which visualize the finest skin lesion of the patient from various distances. Methods: Guidelines were prepared for each and every aspect of photography such as standardization of instrumentation, camera, lighting condition, and distance of skin lesion (which is variable in size). In setup, Nikon D 3300 Camera was used to take photographs of skin lesions, which is one of the high generations digital single lens reflex camera. Guidelines for lighting conditions were prepared using the LUX meter, by achieving a constant lighting condition. For the distance, an artificial skin lesions model of various sizes from 2 mm to 20 cm was made. Standard guidelines were prepared so that the best possible image was captured. Result and Conclusion: Dermatological photography guidelines with consistency and uniformity made diagnosis easier for further reliability and validation purposes in the study. The best possible quality photographs have been achieved through the above said guidelines. Standard guidelines which were prepared for dermatological photography was found appropriate for various purposes such as skin disease diagnosis, and education.